Sie sind auf Seite 1von 2

# Solutions to odd problems Section 5.

3

1a.

1
2
1
2
1 1
2 2
1 1 3
2 3 1
0 0 2
1 1 3
1 2 0 1 2 0
2 3 1
1 3 0 1 3 0
0 0 2
5 5 5 10 5 5 50
1 1
5 10 0 5 4 0 25 25
T T
x
Ax b A Ax A b
x
x
x
x x
x x

= = =

=

= = =

2
25 1

=

b.
1
2
1
2
1 1
2 2
1 1 10
2 1 5
1 2 20
1 1 10
1 2 1 1 2 1
2 1 5
1 1 2 1 1 1
1 2 20
4 1 20 6 1 20
1
1 6 5 1 4 5 23
T T
x
Ax b A Ax A b
x
x
x
x x
x x

= = =

=

= =

115 5
1
0 0 23

= =

c.

1
2
3
1
2
3
1 1 1 4
1 1 1 0
0 1 1 1
1 0 1 2
1 1 1 4
1 1 0 1 1 1 0 1
1 1 1 0
1 1 1 0 1 1 1 0
0 1 1 1
1 1 1 1 1 1 1 1
1 0 1 2
3 0 1
0 3 1
1 1 4
T T
x
Ax b x A Ax A b
x
x
x
x

= = =

1
2
3
6 11 1 3 6 48 8/5
1 1
3 1 11 3 3 18 2
30 30
7 3 3 9 7 36 6/5
x
x
x

= = =

3a.
1 1 1
2 2 2
1
2
1 2 3 1 2 3
1 2 1 1 2 1 6 12 6
2 4 2 2 4 2
2 4 2 2 4 2 12 24 12
1 2 1 1 2 1
1 2 1 2
0 1
x x x
x x x
x
x

= = =

= = +

b.

1 1
2 2
3 3
1
2
3
1 1 3 2 1 1 1 1 1 3 1 1 1 2
1 3 1 0 1 3 2 1 3 1 1 3 2 0
1 2 4 8 3 1 4 1 2 4 3 1 4 8
3 0 6 6
0 14 14 14
6 14 26 26
x x
x x
x x
x
x
x

= =

=

1 1
2 2
3 3
1 0 2 2 2 2 2 2
0 1 1 1 1 1 1
0 0 0 0 0 1
x x
x x
x x

= = = +

5a.
1 1 0 1 1 0
0 1 1 1 0 1 2 0 1 1 0 1 2 1
1 1 3 1 1 1 1 1 1 1 1 1 1 3
2 1 9 2 1 9
6 2 21 4 2 21 58
1 1
2 4 13 2 6 13 36 20 20
m m
b b
m m
b b

= =

= = =

29
1
18 10

=

7.
( ) ( )
( )
2
2 2
1 1 1
0 0 0
/
0
1
0
T
i i i
i i i i T i i i
i i i
i
x y x x y
c c c x y x y x x x
x x
c c c y y x n n y
y
n

= = = =

9a.
( ) ( )
1 1
T T T T
Ax b P A A A A Pb A A A A Ax Ax b

= = = = =

. If b is in the range of A then its projection
is itself.

b.
( ) ( )
1
( ) ( ) 0
T T T
b R A N A Pb A A A A b

= = =

c. If R(A) is a plane through the origin and b is in the plane then its projection is in the plane (itself). If b
belongs to ( ) R A

then it is projected along the normal to the plane to the origin.

11a.
( ) ( ) ( ) ( ) ( )( ) ( )
1 1 1 1 1 1
2 T T T T T T T T T T T T
P A A A A P A A A A A A A A A A A A A A A A A A A A

= = = =

b. This is the inductive step of the proof whose basis step was part (a): So assume that
k
P P = . Then

1 2 k k
P P P PP P P
+
= = = = .

c.
( ) ( ) ( ) ( ) ( )
1
1 1 1
T T
T T
T T T T T T T T T T
P A A A A A A A A A A A A A A A A P

= = = = =

13. Suppose x is a solution to the least squares problem ,
m n
Ax b A

=

. Then
T T
A Ax A b =

. Suppose
n
y

## is also a solution. Then

T T
A Ax A b =

and ( )
0
T T T
A Ay A b A A x y = =

( ) ( )
( ) ( )
T
x y N A A N A x y z N A = =

.
Conversely, if , ( ) y x z z N A = +

then ( )
0
T T T T T T
A Ay A A x z A Ax A Az A b A b y = + = + = + =

solves
the least squares problem.